Platelet‐conditioned media induces an anti‐inflammatory macrophage phenotype through EP4. (3rd December 2020) - Heffron, Sean P.; Weinstock, Ada; Scolaro, Bianca; Chen, Shiyu; Sansbury, Brian E.; Marecki, Greg; Rolling, Christina C.; El Bannoudi, Hanane; Barrett, Tessa; Canary, James W.; Spite, Matthew; Berger, Jeffrey S.; et al.
Abstract: Background: Platelets are increasingly recognized as immune cells. As such, they are commonly seen to induce and perpetuate inflammation; however, anti‐inflammatory activities are increasingly attributed to them. Atherosclerosis is a chronic inflammatory condition. Similar to other inflammatory conditions, the resolution of atherosclerosis requires a shift in macrophages to an M2 phenotype, enhancing their efferocytosis and cholesterol efflux capabilities. Objectives: To assess the effect of platelets on macrophage phenotype. Methods: In several in vitro models employing murine (RAW264.7 and bone marrow–derived macrophages) and human (THP‐1 and monocyte‐derived macrophages) cells, we exposed macrophages to media in which non‐agonized human platelets were cultured for 60 minutes (platelet‐conditioned media [PCM]) and assessed the impact on macrophage phenotype and function. Results: Across models, we demonstrated that PCM from healthy humans induced a pro‐resolving phenotype in macrophages. This was independent of signal transducer and activator of transcription 6 (STAT6), the prototypical pathway for M2 macrophage polarization. Stimulation of the EP4 receptor on macrophages by prostaglandin E2 present in PCM, is at least partially responsible for altered gene expression and associated function of the macrophages—specifically reduced peroxynitrite production, increased efferocytosis and cholesterol efflux capacity, and increased production of pro‐resolving lipid mediators (ie, 15R‐LXA4 ). Conclusions: Platelet‐conditioned media induces an anti‐inflammatory, pro‐resolving phenotype in macrophages. Our findings suggest that therapies targeting hemostatic properties of platelets, while not influencing pro‐resolving, immune‐related activities, could be beneficial for the treatment of atherothrombotic disease.